The Challenges and Solutions for Action of Social Determinants of Health in Iran: A Qualitative Study - Rouhollah Zaboli; Hormoz Sanaeinasab (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Prevention of health inequalities requires attention towards the social determinants of health (SDH). Today, the efforts of countries to reduce health inequalities is throught paying attention to the social determinants of health. The unequal distribution of health in the developing countries is one of the main challenges of health systems which lead to inequality in social status and living conditions. This study aimed to determine the challenges and solutions of social determinants of health in Iran based on expert views. Methods: This study was a qualitative and phenomenological study. The study population consisted of 24 policy makers and experts from the fields of SDH. Purposive stratified non-random sampling was used in this study. Semi-structure interview was used for data collections. Thematic analysis with Nvivo software was used for data analysis. Results: Most experts believed that the economic problems were the major challenges. Lack of long-term planning about social determinants of health, lack of social responsibility and supervision among organizations in the country, the absence of community-oriented individual and organizational perspective and finally clinical approach in health system were the causes of the failure of implementintion of SDH. The most important solution for solving the problem were setting up the health equity monitoring system for identifying the evidence required to justify the policy makers, review the current structure of the office of SDH and conducting further research on the social determinants of health. Conclusion: Paying attention to the SDH can improve health in the community. Promotion of intersectoral collaboration and emphasis on structural determinants and social determinants of health play an important role in reducing health inequalities. It is essential to take this approach by the policy makers and health in all policies finds own places.